2021
DOI: 10.1088/1748-9326/abd78e
|View full text |Cite
|
Sign up to set email alerts
|

How climate change and fire exclusion drive wildfire regimes at actionable scales

Abstract: Extreme wildfires are increasing in frequency globally, prompting new efforts to mitigate risk. The ecological appropriateness of risk mitigation strategies, however, depends on what factors are driving these increases. While regional syntheses attribute increases in fire activity to both climate change and fuel accumulation through fire exclusion, they have not disaggregated causal drivers at scales where land management is implemented. Recent advances in fire regime modeling can help us understand which driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 77 publications
0
51
1
Order By: Relevance
“…We also found that ground/snowpack sublimation decreased when all dead foliage fell to the ground because snowmelt increased with the opening of the canopy. However, this finding differs from that of other studies suggesting that snowpack sublimation can increase with a more open canopy (Biederman et al, 2014;Harpold et al, 2014). The latter can occur because open canopies may allow more snow to reach the ground, which can increase sublimation.…”
Section: Role Of the Long-term Aridity Index (Pet/p )contrasting
confidence: 93%
“…We also found that ground/snowpack sublimation decreased when all dead foliage fell to the ground because snowmelt increased with the opening of the canopy. However, this finding differs from that of other studies suggesting that snowpack sublimation can increase with a more open canopy (Biederman et al, 2014;Harpold et al, 2014). The latter can occur because open canopies may allow more snow to reach the ground, which can increase sublimation.…”
Section: Role Of the Long-term Aridity Index (Pet/p )contrasting
confidence: 93%
“…2018) and that the relative effects of climate and previous fire suppression on fire regimes depend on whether the area was historically fuel or flammability limited (Hanan et al. 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Hanan et al. (2021) propose long‐term average soil moisture as a simple metric to discern whether an area is expected to be fuel or flammability‐limited. Good planning requires understanding the separation of timescales that drive wildfire, both the short‐term and long‐term impacts of climate on vegetation and wildfire and the feedbacks among them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations